2011
DOI: 10.1007/s00296-011-2070-0
|View full text |Cite
|
Sign up to set email alerts
|

Complement components 2 and 7 (C2 and C7) gene polymorphisms are not major risk factors for SLE susceptibility in the Malaysian population

Abstract: There have been numerous studies linking complement components and the pathogenesis of systemic lupus erythematosus (SLE). This is due to their numerous roles in modulating immune responses in the human body. This study examined the association of C2 and C7 genetic polymorphisms with the susceptibility to SLE based on two separate cohorts of patient and control samples from Malaysia. The 28-bp deletion in the C2 exon-intron junction and single nucleotide polymorphism in the 3'untranslated region in the C7 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the C2 gene, a 28 bp deletion is commonly associated with SLE in Caucasians,25 but not in a small Malaysian population 26. C4 is expressed in two isoforms C4A and C4B.…”
Section: Genetic Associationsmentioning
confidence: 99%
“…In the C2 gene, a 28 bp deletion is commonly associated with SLE in Caucasians,25 but not in a small Malaysian population 26. C4 is expressed in two isoforms C4A and C4B.…”
Section: Genetic Associationsmentioning
confidence: 99%
“…Homozygous type 1 C2D is the most commonly inherited defect of complement deficiencies, estimated to be around 1/20,000 among the Western Caucasian population . However, a prevalence study did not show a significant association of type 1 C2D with SLE in Swedish patients , some studies also revealed type 1 C2D was not found in African‐American patients and Asian patients . There is no consistent evidence regarding the predisposition of C2D in different ethnic populations; it appears type 1 C2D might not be a universal factor for SLE susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…C2 deficiency is the most common complement deficiency worldwide and characterized by recurrent infections in early childhood 10 . Autoimmune disorders, particularly SLE were reported with C2 deficiency, but less frequently than the deficiencies of other early complement components 25,27 . Additionally, C2 gene polymorphisms were previously investigated in SLE and did reveal convincing results 9,27 .…”
Section: Discussionmentioning
confidence: 99%